Development of Science Electronic Modules with an Ethnoscience Integrated STEM Approach in Traditional Herbal Medicine Making - Agum Yuda Septajati; Asri Widowati (Universitas Negeri Makassar, 2024)
This research aims to make a feasible and practical science electronic module with an ethnoscience-integrated STEM approach to traditional herbal medicine making for the subtheme of material classification and mixed separation of grade VII junior high school. This research design uses Research and Development (R&D) with a 4D model consisting of Define, Develop, Design, and Disseminate. The software used in developing electronic modules is anyflip. This research was conducted at Junior High School 2 Pracimantoro with the subject of 32 grade VII students. The instruments used in the research include product feasibility sheets, science electronic modules, and product practicality questionnaires. The feasibility and practicality instruments of the product are analyzed quantitatively and qualitative. The results of this study were electronic science modules with an integrated STEM approach to ethnoscience in traditional herbal medicine for the subthemes of material classification and mixed separation declared feasible and declared practical for use in junior high school science learning as evidenced by student response questionnaires obtaining a score of 49.3438 from the maximum number of scores of 60.